Multiple Hepatic and Renal Hydatid Cysts Managed with Laparoscopic Surgery. (17th December 2019) - Kouba, Lamia; Alsaid, Bayan; Almeree, Taisser; Allouche, Mazen; Alshalabi, Abdulghani
Abstract : Cystic echinococcosis is a parasitic disease caused by Echinococcus granulosus. The liver and lungs are the most commonly infected organs. We present the first-of-a-kind case of laparoscopic excision of 8 hydatid cysts, of which seven were in the liver and one was in the kidney of a 40-year-old patient. The patient presented with fatigue and fever and a one-year history of vague abdominal pain. Albendazole was administered before surgical intervention. The postoperative follow-up period was notable for a renal fistula. The patient subsequently underwent CT-guided percutaneous removal of a central hepatic hydatid cyst that was inaccessible using laparoscopic techniques. Cystic echinococcosis is endemic in the Mediterranean region. The growing number of immigrants and refugees from endemic areas could increase the prevalence of the disease in nonendemic countries. Therefore, it is important for physicians worldwide to be familiar with the diagnostic modalities and possible treatment options for hydatid disease.